The Use of Katakana in City Names in Java Island on Japanese Google Map - Martawijaya, Asteria Permata; Radhiya, R Januar (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
Japanese has different characteristics from other foreign languages including having kana letters, kanji andÂ romaji. The kana letters includeÂ hiraganaandÂ katakana. TheÂ katakanaletters are used to write loan word from foreign languages into Japanese. The names from outside Japan are also written usingÂ katakana. This study discusses about the writing of names of cities in Java island into JapaneseÂ katakanawhich contained in Japanese version of Google Maps. The aims of this study areÂ to know how google.map.jp write the names of cities in Java island using JapaneseÂ katakanaand what pattern did they use to write those cityâ€™s names. The analysis conducted by using descriptive method. The results of this study revealed that in Japanese version of Google Map, there are 62 city names written inÂ katakana, while the rest are written inÂ romaji. There are eight patterns found in writing the name of the cities usingÂ katakana. Those are including writingÂ katakanabased onÂ Hepburnstyle using the KVKV pattern, adding vowels to each closed syllable sound, writing â€œrâ€ for the sound of â€œlâ€, and syllable â€œciâ€ written as â€œchi (ãƒ)â€ or â€œshi (ã‚·)â€.